Application of ez-enzyme in bioremediation of oily sludge - Ho, Jenny (Penerbit UTM Press, 2008)
Sludge farming is commonly used in petroleum refinery as a method of treatment for oily waste containing degradable constituents into materials that are not hazardous to human health or the environment. The sludge is left on a designated plot of land to be biodegraded naturally, but the process could take a considerable length of time. In this study, an enzyme known as EZ-Enzyme was tested to bioremediate the oily sludge sample in a laboratory scale experiment. Results shown that there was a consistent reduction in the oil and grease (O&G) content of the tested sludge (~ 60% in average). The O&G content decreased with increase in the concentration of enzyme. The O&G content in a sludge sample decreased the most with the application of 100 pm EZ-Enzyme, which decreased from 8% to 2% within a period of nine weeks. In general, the temperature and pH of the system were maintained at optimum condition, which were 35Â°C and pH 7 respectively. The quality of the leachate was also improved by the end of the study, where chemical oxygen demand (COD) was 25 mg/l and pH was 6.45 respectively